The Effect of Education on Increasing Student Enthusiasm for Learning in the Transition Period of Online to Offline Learning - Muhamad Rivaldi; Rina Maryanti (Indonesian Journal of Educational Research and Technology, 2023)
This study aims to find out the reason for the impact of the increase in enthusiasm for learning in the transition period of online to offline learning. This research was conducted on 12 students from State Junior High School 12 Bandung, Indonesia, who came from grades 7, 8, and 9. This research was conducted using a qualitative method with 3 stages, namely (i) the dissemination of the pre-test questionnaire, (ii) the provision of education to increase the enthusiasm for learning with video media, and (iii) the dissemination of the questionnaire post-test. The results obtained in the form of the average value of the pretest was 52.5 and the average post-test was 87.5 which showed that the student's post-test score increased significantly. This is due to the lack of education of students on the spirit of learning, and they are not used to offline learning. From the results of the study, it can be interpreted that the provision of education to increase the enthusiasm for learning in the transition period of online to offline learning with video media is influential and effectively used on students. This research is expected to have an impact on increasing student enthusiasm for learning which will affect student learning outcomes.